Kejahatan Siber dengan Metode DDOS Attack terhadap Website dalam Perspektif Fiqih Jinayah - Eko Wahyu Ramadani; Rustam Dalhar Karnadi Apolo Harahap; Riza Fibriani (CV Rewang Rencang, 2025)
Cybercrime using the DDoS attack method against a website is a crime that aims to paralyze the website by flooding the webserver traffic, resulting in damage to the website system. The threat of this method is very real but law enforcement is not optimal, one of the reasons is because the rules for criminal sanctions are unclear. This research attempts to formulate criminal sanctions based on the Jinayah fiqh conception. This research uses qualitative methods with a juridical-normative approach, the data used in this research comes from the book Al-Qawâ'id wal-Ushûl al-Jûmi'ah wal-Furûq wat-Taqâsîm al-Badî'ah an-Nâfi'ah , by Shaykh 'Abdur-Rahmân as-Sa'di, tahqiq: Dr. Khalid bin 'Ali bin Muhammad al-Musyaiqih, Darul wathan, print II. The results of this research are that perpetrators can be subject to criminal sanctions for jarimah ta'zir in the form of fines (ghurammah) and prison sentences.